2002
DOI: 10.1097/00001756-200212200-00037
|View full text |Cite
|
Sign up to set email alerts
|

Brief exposure to NaCl during early postnatal development enhances adult intake of sweet and salty compounds

Abstract: Taste acceptance involves both innate and acquired components. We observed an increased acceptance of salty and sweet solutions in adult rats whose tongues had been exposed to an NaCl-enriched milk formula during one day of early postnatal development. This behavioral effect was associated with changes in the norepinephrine system of the basolateral amygdala. No other changes in behavior, food intake, body weight, blood or metabolic parameters of the NaCl-exposed adult rats were identified. The data suggest a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Weaned lambs whose mothers ingested a high-salt diet during pregnancy did not show any difference in the feeding behaviour when offered a choice between a control-and high-salt feed, in comparison with non-exposed lambs. These results are surprising because (i) rat offspring born to mothers consuming high salt during gestation and/or during early postnatal development have shown an increased preference for salt (Smriga et al, 2002;Curtis et al, 2004) and (ii) in sheep, postnatal responses to a flavour can be influenced by prenatal exposure to this flavour via maternal ingestion (Simitzis et al, 2008). The ewes in the current study were fed a high-salt diet during pregnancy only, and not after parturition, and this may partly explain the difference in the development of taste preferences postnatally.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Weaned lambs whose mothers ingested a high-salt diet during pregnancy did not show any difference in the feeding behaviour when offered a choice between a control-and high-salt feed, in comparison with non-exposed lambs. These results are surprising because (i) rat offspring born to mothers consuming high salt during gestation and/or during early postnatal development have shown an increased preference for salt (Smriga et al, 2002;Curtis et al, 2004) and (ii) in sheep, postnatal responses to a flavour can be influenced by prenatal exposure to this flavour via maternal ingestion (Simitzis et al, 2008). The ewes in the current study were fed a high-salt diet during pregnancy only, and not after parturition, and this may partly explain the difference in the development of taste preferences postnatally.…”
Section: Discussionmentioning
confidence: 98%
“…The ewes in the current study were fed a high-salt diet during pregnancy only, and not after parturition, and this may partly explain the difference in the development of taste preferences postnatally. In rats, salt preference is increased if the pups are exposed to salt during the postnatal period (Smriga et al, 2002;Curtis et al, 2004). Mistretta and Bradley (1983) showed that young taste bud cells do not have the same salt response characteristics as mature cells, and a changing neural substrate underlies development of salt taste function, both pre-and postnatally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-natal salt exposure and behavioral programming -preference for salt Rats exposed to high salt, either pre-and/or postnatally in early life, but not later at 14 to 15 days of life, develop a preference (when offered a choice) for salt at adult ages (Smriga et al, 2002;da Silva et al, 2003) suggesting that the time of exposure to salt is important. In addition, calves born from cows that received supplementary sodium during pregnancy have a higher appetite for sodium (desire to eat), indicating that appetite regulation of the offspring could be entrained by the sodium intake of the dam during late pregnancy (Mohamed and Phillips, 2003).…”
Section: Fetal Programming During Intra-utero Exposure To Saltmentioning
confidence: 99%
“…The absence of preference for salt in the offspring might have been influenced by the termination of feeding the high-salt diet immediately at birth. In rats, salt preference is increased, if the pups are exposed to salt during the postnatal period (Smriga et al, 2002;Curtis et al, 2004). It is also possible that fetal programming of dietary salt preferences does not occur as strongly in sheep as it does in rats or cattle.…”
Section: Fetal Programming During Intra-utero Exposure To Saltmentioning
confidence: 99%